MENALAR PARADOKS KONSEP NASIONALISME, GENERASI EMAS, DAN TEKNOKRASI: PERSPEKTIF ILMU SOSIAL KRITIS - Kenoba, Marianus (Program Studi Pendidikan Sejarah Universitas Flores, 2024)
AbstractNationalism constitutes a fundamental concept within modern social sciences. However, its interpretation and system of meaning are not always neutral, often leading to paradoxes. This paradox arises from the notion that pragmatic nationalism is influencing the younger generation, which, by 2045, has been conceptualized within the sociopolitical framework as the